ANALISIS KUAT LENTUR DAN KUAT TEKAN PADA LIMBAH BOTOL PLASTIK BAHAN PEMBENTUK GRC - Suripto; Tri Wulan Sari; Denny Yatmadi (Politeknik Negeri Jakarta, 2023)
Plastic is one of the items that cannot be separated from our daily lives. GRC (Glassfibre Reinforced Cement) is a building material similar to concrete, made of cement reinforced by fiberglass which has alkali resistant properties. The purpose of this study was to analyze the flexural strength and compressive strength of GRC building materials with plastic bottle substitution. The type of research used experimental. The method carried out by replacing several compositions of fiber, plastic processed from plastic bottle waste and fiber with plastic waste in the GRC-forming mixture to utilize plastic waste to reduce the use of fiber glass. The research method used starts from the study of literature, manufacture of test materials, manufacture of test specimens, testing of flexural strength and compressive strength, then data analysis and discussion are carried out. The results obtained were that the flexural strength of the GRC material specimen with a substitution of 3.5% fiber as measured by the weight of the mortar is the largest flexural strength compared to other material substitutions. With the average flexural strength value obtained is 1.81 MPa or Fs = 18.48 kg/cm2. From the substitution of 1.75% fiber plus 1.75% plastic bottle waste to the GRC-forming material, there was a decrease in the average flexural strength value of 1.44 MPa or about 10.10%, while the act of replacing plastic bottled waste to the GRC-forming material decreased. the average flexural strength value is 3.27 MPa or about 22.93%.